Introduction to The Spiral Dynamics and The Spiral Coriolis Force (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The spiral dynamics of a point-like body of mass m in spiral differential geometry are introduced. New ideal motions have been studied, the uniform spiral motion and the uniform spiral-polar motion. The analysis is proposed by comparing the ideal spiral motions with the ideal circular motions. The theoretical forces acting on a point-like body of mass m moving in spiral frames were analyzed. The spiral and polar components of the Coriolis forces were compared.